On the Separation Theorem of Stochastic Systems in the Case Of Continuous- Discrete Observation Channels with Memory; Journal of Physics: Conference Series; Vol. 659 : Advanced Control and Diagnosis (ACD 2015) - Rozhkova S. V. Svetlana Vladimirovna; Рожкова В. И. Валентина Ивановна; Lasukov V. V. Vladimir Vasilievich; Devyashina E. V. Elena Vadimovna (2015, 2015)
Title screen